Early Removal of Foleys Catheter within 48 Hours of Transurethral Resection of the Prostate - Mahmood Ahmed Memon, Shahnawaz Rafique Rajper, Shah Muhammad Noonari, Muhammad Babar Baig, Bilal Suri, Muhammad Shahid Bhatti, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To study outcomes of early removal of foley’s catheter after transurethral resection of prostate (TURP). Study Design and Duration: This is a cross sectional study completed in six months duration from May to October 2022. Setting: study was conducted in the department of urology Shaheed Mohtarma Benazir Bhutto Medical College. Methodology: All male patients above 50 years of age with prostate more than 30 gm and less than 60 grams with definitive indication of TURP were included in this study. Those with age less than 50 years, prostate less than30 gram, more than 60, patient with cerebrovascular disease or psychiatric disorder and history of stricture urethra were not included in this study. Results: Total 60 patients were included in this study with maximum age 70 years and minimum age was 55 years. Average size of prostate determined by trans-abdominal ultrasound was 52 grams, maximum size was76 grams and minimum size was 30 grams. Foleys catheter was removed in all patients on the second postoperative day within 48 hours after TURP. Patient voided with good stream after Foley’s removal. Out of sixty patients one patient (1.7%) developed urinary retention immediately after Foley’s removal who was recatheterized and Foley’s was kept for further three days and trial of catheter was given which was successful. One patient (1.7%) developed mild hematuria and Foley’s was kept for 2 days and trial was successful. Conclusion: Early removal of Foley’s reduces hospital stay, early return to work, prevents catheter related side effects and reduces patients anxiety due to catheter. Keywords: Foleys Catheter, TURP, Catheterization, BPH